Vacunagate: ¿era posible justificar moralmente el caso peruano? - Ibáñez, Franklin (2022)
This article studies the Vacunagate: a scandal during the early-2021 in Peru due to irregular inoculation of the Sinopharm candidate vaccine against COVID-19 during its experimental stage. We analyze the morality of this case in order to elucidate the public discussion on the conduct and supervision of clinical trials within the context of a Pandemic. We evaluate whether two actions were morally justifiable: (1) the use of a vaccine outside of a clinical trial, and (2) prioritizing some groups in that unusual allocation. These groups are (i) research staff of the clinical trial, (ii) public health officials leading the fight against the Pandemic, (iii) human acquaintances of the first two groups, and (iv) others. As this article is on applied ethics, it follows its methodology: we define the moral, or philosophical, framework and its later applied to the case. The ethical framework for our analysis will be constituted by two kinds of moral principles: democratic and utilitarians. First, we address two principles common to contemporary democracies: equal value for all human beings and the necessary public deliberation on issues of common interest. Second, without contradicting these democratic principles, we assess the actions under the application of utilitarian reasoning. Finally, based on the WHO MEURI Guide and the mentioned ethical framework, we describe the missing conditions under which both actions could have been morally justified.